Updated global epidemiology atlas of human prion diseases - Gao, Li-Ping; Tian, Ting-Ting; Xiao, Kang; Chen, Cao; Zhou, Wei; Liang, Dong-Lin; Cao, Run-Dong; Shi, Qi; Dong, Xiao-Ping (Frontiers in Public Health, 2024)
Introduction Human prion disease (PrD), a group of fatal and transmissible neurodegenerative diseases, consists of Creutzfeldt–Jakob disease (CJD), kuru, fatal familial insomnia (FFI), Gerstmann-Sträussler-Scheinker disease (GSS), and variably protease-sensitive prionopathy (VPSPr). The emergence of bovine spongiform encephalopathy (BSE) in cattle and variant CJD (vCJD) has greatly threatened public health, both in humans and animals. Since the 1990's, dozens of countries and territories have conducted PrD surveillance programs. Methods In this study, the case numbers and alternative trends of different types of PrD globally and in various countries or territories from 1993 to 2020 were collected and analyzed based on the data from the websites of the international and national PrD surveillance programs, as well as from relevant publications. Results The total numbers of the reported PrD and sporadic CJD (sCJD) cases in 34 countries with accessible annual case numbers were 27,872 and 24,623, respectively. The top seven countries in PrD cases were the USA (n = 5,156), France (n = 3,276), Germany (n = 3,212), Italy (n = 2,995), China (n = 2,662), the UK (n = 2,521), Spain (n = 1,657), and Canada (n = 1,311). The annual PrD case numbers and mortalities, either globally or in the countries, showed an increased trend in the past 27 years. Genetic PrD cases accounted for 10.83% of all reported PrD cases; however, the trend varied largely among the different countries and territories. There have been 485 iatrogenic CJD (iCJD) cases and 232 vCJD cases reported worldwide. Discussion The majority of the countries with PrD surveillance programs were high- and upper-middle-income countries. However, most low- and lower-middle-income countries in the world did not conduct PrD surveillance or even report PrD cases, indicating that the number of human PrD cases worldwide is markedly undervalued. Active international PrD surveillance for both humans and animals is still vital to eliminate the threat of prion disease from a public health perspective.